2014
DOI: 10.1074/jbc.m113.544122
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Oxidative Endoplasmic Reticulum Stress Response Caused by Deficiency of Thyroid Hormone Receptor α

Abstract: Background: Endoplasmic reticulum (ER) stress is involved in ␤-cell failure and apoptotic death. Results: Upon endogenous TR␣ knockdown, ER stress significantly enhanced apoptosis in pancreatic ␤-cells. Conclusion: TR␣ facilitates reduced apoptosis in pancreatic ␤-cells under ER stress. Significance: TR␣ is coupled to stress response modulation and improved survival of pancreatic ␤-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The protocols for Western blot analysis and real-time PCR were previously described 45 . Nuclear or cytoplasmic cell extracts were prepared using the NE-PER kit (PIERCE) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The protocols for Western blot analysis and real-time PCR were previously described 45 . Nuclear or cytoplasmic cell extracts were prepared using the NE-PER kit (PIERCE) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a study showed that TH receptor disorder is closely related to pancreatic β cell survival after endoplasmic reticulum (ER) stress. This study found higher levels of TR α -activated transcription factor 4 (ATF4) and heme oxygenase 1, which facilitates adaptation to oxidative ER stress in the pancreas of HFD-treated mice [ 80 ]. In addition, it is known that glucose sensing is the initial event for glucose-stimulated insulin secretion.…”
Section: Roles Of Thyroid and Thyroid Hormone In Pancreas Pathogenmentioning
confidence: 99%
“…The study was approved by the Animal Research Committee of Kyushu University and carried out in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals, and experimental procedures were based on the Guidelines of the Committee for Animal Care and Use of Kyushu University. TRa-deficient mice (TRa 0/0), which lack all known products of the TRa gene, were created in the laboratory of Dr. Samarut, as described elsewhere (Macchia et al, 2001;Takahashi et al, 2014). The mice were maintained at the University of Chicago for several generations and back-crossed more than 10 times onto the C57BL/6 background before TRa 0/0 male and female mice were given to Dr. Suzuki's lab (Fukushima Medical University, F, Japan), and were then kindly given to the present authors by Dr. Suzuki with the permission of Dr. Samarut.…”
Section: Animalsmentioning
confidence: 99%